1978
DOI: 10.1007/bf00442366
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral circulation in the newborn: Interaction of peripheral blood flow, blood pressure, blood volume, and blood viscosity

Abstract: Peripheral blood flow and systolic blood pressure (strain-gauge plethysmograph), blood volume (Evans blue) and whole blood viscosity (cone-plate viscometer) have been measured in 66 premature and full-term infants 6 to 144h of age. Blood flow and blood volume were moderately decreased in the infants with respiratory distress. Highly significant (P less than 0.001) correlations were found between blood flow and blood volume (r = 0.77), blood pressure and blood volume (r = 0.50), peripheral resistance and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The results of the present study and previously reported results are shown in Table 2 (13)(14)(15)(16)(17). Our data are similar to the previously reported data.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study and previously reported results are shown in Table 2 (13)(14)(15)(16)(17). Our data are similar to the previously reported data.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, RBC vel inversely correlated with mean systolic blood pressure. This seems surprising since past studies have shown that blood pressure in premature infants correlates with blood flow (35). In those studies, blood flow was measured with venous occlusion plethysmography, which will determine arterial blood flow in vessels of all sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our values probably are a mixture of venous and arterial flow velocities. Previous studies have shown that resistance and viscosity play a crucial role in neonatal peripheral blood flow (35,36). Both undergo marked changes in the first days of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of red cell mass causes impairment of oxygen transport to the tissues during the entire progress of the respiratory disease: A low red cell mass reflects a low blood volume at the time of cord-clamping [28,32]. Hypovolaemia, probably one major side effect of intra-partum asphyxia, causes marked reduction of cardiac output [26] and of peripheral blood flow [18,35] in the newborn. Hypoxia may further reduce cardiac output [26] and disturb the microcirculation [20], and this is probably mediated by catecholamines [21].…”
Section: Discussionmentioning
confidence: 99%